Alimentando a su Bebé - Linda B. Bobroff (EDIS, 2006)
Revised! FCS-8545-Span (previously FCS-8548), a 4-page fact sheet by Linda B. Bobroff, is the Spanish version of "Feeding Your Baby". This document will help parents develop a close relationship with their infants through feeding. Provides information on breast milk and formula and on ways to nurture the bonds between parent and child. This version is updated with new color art, new recommendations, and revised wording throughout. Published by the UF Department of Family Youth and Community Sciences, October 2006.